2010
DOI: 10.1055/s-0030-1250378
|View full text |Cite
|
Sign up to set email alerts
|

Kurrikulare Ultraschallausbildung am Bewegungsapparat: Einfluss der anatomischen Vorbildung auf die Weitergabe von Basis-Skills an der Schulter

Abstract: Although deficits in theoretical knowledge cannot be compensated for, basic MSUS content appears to be adequately transferable to students with limited anatomic knowledge. Thus, an early implementation of MSUS during medical school education would be prudent, provided that the training is performed by an experienced MSUS operator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A possible explanation might be the fact that we used student-teachers as lecturers. Minimally instructed student-teachers can be employed to teach anatomically skilled students, whereas medical experts should be used in earlier stages of anatomical education [11]. Tolsgaard et al and Shiozawa et al postulated that the specific training of student-teachers was an absolute necessity for success in the environment of peer-assisted learning [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation might be the fact that we used student-teachers as lecturers. Minimally instructed student-teachers can be employed to teach anatomically skilled students, whereas medical experts should be used in earlier stages of anatomical education [11]. Tolsgaard et al and Shiozawa et al postulated that the specific training of student-teachers was an absolute necessity for success in the environment of peer-assisted learning [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Herewith, students receive a profound background that forms the basis for the acquisition of further skills in different subspecialties [7]. Previous studies suggested that students may learn the basics of ultrasound with comparatively little didactic investment [8-11]. However, only two studies specifically evaluated musculoskeletal ultrasound (MSUS) [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing professional and student tutors by questioning participants of a pharmacology course, it became evident that neither specialized competence nor teaching experience had any significant influence on the students' results in the written final examinations [30]. Positive experiences were also reported regarding the student tutor system in the area of ultrasound courses [17,18]. In the above course, the quality of the tutors was assessed by the participants with 1.42 and 1.51, respectively.…”
mentioning
confidence: 99%